2006
DOI: 10.1093/jnci/djj053
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Active-Controlled Trial of Every-3-Week Darbepoetin Alfa for the Treatment of Chemotherapy-Induced Anemia

Abstract: Patients with chemotherapy-induced anemia can safely and effectively be treated with 500 microg of darbepoetin alfa every 3 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 37 publications
6
59
1
5
Order By: Relevance
“…A recent large phase III randomised study compared DA weekly vs. Q3W in patients with non-myeloid malignancies treated for CIA [5]. Q3W dosing of DA proved to be noninferior to weekly in terms of efficacy (Hb endpoints, RBC transfusion rates and impact on QoL), and the adverse event profile was similar in both arms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent large phase III randomised study compared DA weekly vs. Q3W in patients with non-myeloid malignancies treated for CIA [5]. Q3W dosing of DA proved to be noninferior to weekly in terms of efficacy (Hb endpoints, RBC transfusion rates and impact on QoL), and the adverse event profile was similar in both arms.…”
Section: Discussionmentioning
confidence: 99%
“…Evolution of Hb over time was analysed with Kaplan-Meier analysis. Similar to the analyses conducted in phase III randomised study [5], Hb endpoints were reported using all available Hb values and also disregarding Hb values within 28 days after any transfusion. Results were reported as Kaplan-Meier rates after 12 weeks of therapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extended dosing was shown to have comparable efficacy and safety profiles to QW dosing with respect to raising Hb levels, 19,20 and reducing RBC transfusion requirements. [21][22][23][24] Importantly, the administration of DA Q3W represented an opportunity to synchronize ESA treatment with many chemotherapy regimens in clinical practice. 25 Chemotherapy has a myelosuppressive effect and as bone marrow had a hypothesized role in ESA clearance, the question was raised as to whether the efficacy of DA was different when administered synchronously or asynchronously with chemotherapy.…”
Section: Early 1990s To Mid-2000s: Developmentmentioning
confidence: 99%
“…Once-weekly (Q1W) administration with all ESAs has become the preferred treatment modality (6,7). Darbepoetin α has also been licensed for use once every 3 weeks (Q3W) in cancer patients with chemotherapy-induced anemia (8). Continuous erythropoietin receptor activator (C.E.R.A.)…”
Section: Introductionmentioning
confidence: 99%